2012
DOI: 10.3168/jds.2011-4447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subacute ruminal acidosis challenges on fermentation and endotoxins in the rumen and hindgut of dairy cows

Abstract: The effects of a grain-based subacute ruminal acidosis (SARA) challenge (GBSC) and an alfalfa-pellet SARA challenge (APSC) on fermentation and endotoxins in the rumen and in the cecum, as well as on endotoxins in peripheral blood, were determined. Six nonlactating Holstein cows with cannulas in the rumen and cecum were used in the study. A 3×3 Latin square arrangement of treatments with 4-wk experimental periods was adopted. During the first 3 wk of each experimental period, all cows received a diet containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
264
14
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(312 citation statements)
references
References 33 publications
27
264
14
7
Order By: Relevance
“…Although the grain level in our study was not as high as that previously reported, the 45% NFC is sufficient to promote the growth of gram negative bacteria, which is correlated with the levels of rumen LPS (Zebeli and Ametaj, 2009). Although the LPS levels in this study are in relative agreement with those published earlier (Khafipour et al, 2009a;Li et al, 2012), it is not clear whether they are in sufficient concentration to favour transmigration and to trigger an immune response. In order for such a response to exist, free LPS must be transported to effector cells of the immune system by the soluble acute phase protein, LBP (Muta and Takeshige, 2001).…”
Section: Physiological Parameterssupporting
confidence: 41%
“…Although the grain level in our study was not as high as that previously reported, the 45% NFC is sufficient to promote the growth of gram negative bacteria, which is correlated with the levels of rumen LPS (Zebeli and Ametaj, 2009). Although the LPS levels in this study are in relative agreement with those published earlier (Khafipour et al, 2009a;Li et al, 2012), it is not clear whether they are in sufficient concentration to favour transmigration and to trigger an immune response. In order for such a response to exist, free LPS must be transported to effector cells of the immune system by the soluble acute phase protein, LBP (Muta and Takeshige, 2001).…”
Section: Physiological Parameterssupporting
confidence: 41%
“…In our model, microscopic images revealed that the extent of damage to the rumen following a HG challenge was limited to epithelial sloughing and to a lesser extent tight junction degradation (Steele et al 2011a); this sloughing was restored with an epithelium that was adapted to accommodate the HG challenge. Since the rumen epithelium became slightly permeable, it is possible that some microorganisms penetrated to the submucosal layers, since elevated levels of Lipopolysaccharide Binding Protein (LPSBP) were detected using the same model in subsequent experiments (Li et al, 2012;Steele et al, 2012). Because of the limited extent of pathogenic organisms and LPS infiltration, the inflammatory phase of the wound healing cascade was extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in acute phase proteins, also referred to as an acute phase response, could be caused by the translocation of LPS from the digestive tract into the peripheral circulation (Emmanuel et al, 2008;Plaizier et al, 2012). Gozho et al (2007), Emmanuel et al (2008), Khafipour et al (2009b), and Li et al (2012b) reported that increased grain feeding increased the concentration of LPS in rumen and cecal digesta, and the concentration of acute phase proteins in peripheral blood. Increasing grain inclusion to induce SARA in dairy cows results in major changes in the microbiota of rumen digesta, including increases in starch-and soluble sugar-fermenting bacteria, lactic acid-fermenting bacteria, and Escherichia coli, as well as a reduction in the population of gram-negative Bacteroidetes (Nagaraja and Titgemeyer, 2007;Khafipour et al, 2009c).…”
Section: Introductionmentioning
confidence: 98%
“…These energy-dense diets are primarily obtained with moderate to high inclusion rates of grain. However, these types of diets can affect cattle health, as increases in grain feeding have been associated with a heightened risk for SARA, increased concentrations of endotoxic LPS in the gut, as well as increased concentrations of acute phase proteins in peripheral blood (Gozho et al, 2007;Emmanuel et al, 2008;Li et al, 2012b).…”
Section: Introductionmentioning
confidence: 98%